Risk factors of cleft lip and/or palate in neonates of Mother - Child National Teaching San Bartolome Hospital in the period 2000 to 2009 - Torres Durand, Marco Antonio (2011)
The aim of this study was to evaluate retrospectively the risk factors for cleft lip and/or palate. It was selected a sample of 45 children with a cleft lip and/or palate and 45 healthy newborns at Mother Child National Teaching San Bartolome Hospital from January 2000 to December 2009 and their respective biological mother to assess retrospectively the conditions under which this was formed during the first trimester of pregnancy. It was found that the prevalence of cleft lip and/or palate was 0,17 % ie, 1,7 per thousand live births. The male gender (RRI 1.7), maternal age (RRI18.4; RRI23,9), family history of cleft lip and/or palate (RRI 3,3), number of previous pregnancies (RRI1 4,6; RRI2 1,1) are risks factors. The history of infections, radiation and medication during the first trimester of pregnancy were not found to be risks factors.